2002
DOI: 10.2527/2002.80112953x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of male pigs immunized against GnRH is related to the time of onset of biological response1

Abstract: In this study, the performance of male pigs immunized against GnRH was determined in relation to the onset of their biological response to the immunization. Pigs were immunized at 9 and 17 wk of age and were housed in a pen together with both a surgically castrated and an intact boar littermate. Feed intake was restricted to 2.8 to 3.2 times maintenance requirement for energy. Animals were weighed weekly and slaughtered at 108 kg BW. Depending on the time of onset of the response after immunization in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 17 publications
6
30
1
1
Order By: Relevance
“…As could be expected, backfat thickness in IC increases with the time between V2 and slaughter (Lealiifano et al, 2011). IC submitted to an early vaccination schedule (Falvo et al, 1986) or exhibiting a response after the first vaccination (early responders described by Turkstra et al, 2002) may actually be fatter than SC.…”
Section: Immunocastrates -Entire Malesmentioning
confidence: 73%
See 1 more Smart Citation
“…As could be expected, backfat thickness in IC increases with the time between V2 and slaughter (Lealiifano et al, 2011). IC submitted to an early vaccination schedule (Falvo et al, 1986) or exhibiting a response after the first vaccination (early responders described by Turkstra et al, 2002) may actually be fatter than SC.…”
Section: Immunocastrates -Entire Malesmentioning
confidence: 73%
“…This could be explained with an early response to the vaccination. Indeed, Turkstra et al (2002) observed that in some pigs (qualified as early responders), LH and testosterone levels were reduced after V1. After the second vaccination, IC produce a large quantity of antibodies, sufficient for the neutralization of all secreted GnRH.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to a rapid immunocastration effect in these pigs. In a study by Turkstra et al (2002), where a different anti-GnRH vaccine was used, 50% of the pigs had low levels of plasma testosterone and diminished testicular function already before the second vaccination. Before slaughter, mounting was also absent in standard vaccinated pigs, but was still present among the entire male pigs at the same level as previously.…”
Section: Resultsmentioning
confidence: 99%
“…It also offers welfare advantages due to the absence of castration pain and stress (Prunier et al, 2006). Results of some studies also report higher growth rates for entire males than for C (Andersson et al, 1997;Turkstra et al, 2002). However, responses of anabolic steroids production by entire males are inconsistent because performance differences between entire males and castrates depend on genotype and housing conditions.…”
Section: Introductionmentioning
confidence: 99%